Power trading Raft consensus mechanism considering green certificate and carbon emission weights - Xiong, Xiaoping; Liu, Yinzheng; Qu, Huijie; Cai, Yiming (Frontiers in Energy Research, 2023)
The consensus mechanism is a critical technology in the power trading blockchain distributed power trading platforms, which are gradually being applied and promoted to achieve the "dual carbon" goal. Green-certificate trading and carbon emission trading systems help mobilize power generation enterprises to increase the generation of and investment in renewable energy, thereby becoming important factors in distributed power trading. Therefore, they should also be considered as factors in the consensus mechanism. This article first evaluates the green-certificate weight based on whether nodes possess green certificates, evaluates the carbon emission weight based on the carbon emission settlement of nodes in the previous cycle, and constructs a mechanism to evaluate a node's weight. An improved Raft consensus algorithm based on node weight is then proposed. Nodes with greater weights are more likely to become leading nodes, promoting active compliance and green consumption by nodes and reducing carbon emissions. A simulation shows that the improved Raft consensus mechanism enhances the reliability of leading nodes, improves the efficiency of the distributed power transaction, increases the generation of renewable energy, and encourages the consumption of new energy.